Nível socioeconômico e as relações com funções executivas e linguagem em crianças no início da alfabetização - Nikaedo, Carolina Cunha [UNIFESP] (2015)
Common sense tells us that socioeconomic status (SES) affects cognitive development. However, it remains unclear the impact of SES in different cognitive domains, as which variables of this construct are the most significant to children development. Family SES measured by the following three variables: schooling and profession of the main caregiver, and stimulation at home. This research reports the effects of SES on the language and executive function in children from public schools in Sao Paulo city. This longitudinal study followed children aged from 6 to 8 years in two waves. One hundred and fourteen children were assessed at wave 1 and one year after 46 children were followed up at wave 2. Regression models were carried out to test whether SES measures are good predictors of cognitive abilities. Parental schooling was a significant predictor of language accounting for 14% of variance, although it did not explain the variance in academic achievement one year later. For the second wave, language had a huge impact on reading achievement accounting for 22,4% of the variance found. Hypothesis for these findings are discussed as well the longitudinal data. Suggestions for policymaking based on the data are described and also the contribution for the field.